2015
DOI: 10.4238/2015.may.11.17
|View full text |Cite
|
Sign up to set email alerts
|

Role of a liver fatty acid-binding protein gene in lipid metabolism in chicken hepatocytes

Abstract: ABSTRACT. This study investigated the role of the chicken liver fatty acid-binding protein (L-FABP) gene in lipid metabolism in hepatocytes, and the regulatory relationships between L-FABP and genes related to lipid metabolism. The short hairpin RNA (shRNA) interference vector with L-FABP and an eukaryotic expression vector were used. Chicken hepatocytes were subjected to shRNA-mediated knockdown or L-FABP cDNA overexpression. Expression levels of lipid metabolismrelated genes and biochemical parameters were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our results suggest that a wheat-based diet promotes the absorption of n-3 and its long-chain metabolites for β-oxidation in the liver. This inference is supported by Gao [35], who investigated how L-FABP helped lipid metabolism in the chicken liver by increasing the expression of its transcriptional regulator PPAR-α. Contrary to our finding, Poirier et al [36] reported the over-expression of L-FABP in mice given n-6 enriched sunflower oil.…”
Section: Discussionmentioning
confidence: 89%
“…Our results suggest that a wheat-based diet promotes the absorption of n-3 and its long-chain metabolites for β-oxidation in the liver. This inference is supported by Gao [35], who investigated how L-FABP helped lipid metabolism in the chicken liver by increasing the expression of its transcriptional regulator PPAR-α. Contrary to our finding, Poirier et al [36] reported the over-expression of L-FABP in mice given n-6 enriched sunflower oil.…”
Section: Discussionmentioning
confidence: 89%
“…Studies have shown that the transcriptional regulation of FABP gene is related to the PPAR signaling pathway. As a key regulator of liver lipid metabolism, The way FABP1 affects lipid metabolism may be through the regulation of PPARα in chicken liver cells (He et al 2013;Spann et al 2006;Gao et al 2015). Studies have shown that resveratrol can improve lipid deposition by regulating the expression of genes related to PPAR signaling pathway in chicken liver, thereby alleviating the damage of hepatocyte steatosis (Luo 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid-binding proteins (FABPs) have attracted interest from many researchers owing to their diverse biological functions, including fatty acid oxidation (Gan et al 2015), transport (Storch and Thumser 2000), and lipid storage (He et al 2013). FABP1, FABP3, and FABP4 were widely reported as vital candidate genes for IMF deposition in chicken (Gao et al 2015;. According to Li et al, the liver of laying hens manifested over-expression of FABP1 and FABP3 levels compared to the juvenile hens to meet the requirement of laying eggs (Li et al 2015).…”
Section: Discussionmentioning
confidence: 99%